Relationship Between Advertising Expenditures and Earnings of The UK Firms - Maqsood Iqbal Qureshi (Journal of Accounting and Management Information Systems (JAMIS), 2018)
This article studies the asset value of the UK firms advertising expenditures by estimating the relation between advertising expenditures and earnings for a large cross-section of the UK firms for the period from 1999 to 2003 and reports that advertising expenditures are significantly correlated with earnings. The results indicate that advertising expenditures contribute to earnings afar the era these expenditures are incurred. These expenditures are positively significantly correlated with earnings at least up to four years after the year of the expenditure. Additionally, this article also examines the possible differential media advertising asset value effects on earnings and results do not appear to report asset value differences across electronic and print media advertising expenditures. The overall results of this study suggest positive contribution and long lived effects of advertising expenditures to earnings and hold important implications for policy makers and standard setters.
Keywords: M4; 650; advertising; intangible; earnings; media advertising